Setleis syndrome in Mexican-Nahua sibs due to a homozygous TWIST2 frameshift mutation and partial expression in heterozygotes: review of the focal facial dermal dysplasias and subtype reclassification. Issue 10 (19th September 2011) - Cervantes-Barragán, David E; Villarroel, Camilo E; Medrano-Hernández, Alma; Durán-McKinster, Carola; Bosch-Canto, Vanessa; del-Castillo, Victoria; Nazarenko, Irina; Yang, Amy; Desnick, Robert J
Abstract : Background: The focal facial dermal dysplasias (FFDDs) are a group of inherited disorders of facial development, characterised by bitemporal or preauricular scar-like defects, the former resembling 'forceps marks'. Recently, different homozygous TWIST2 nonsense mutations were reported in unrelated Setleis syndrome (FFDD Type III) patients from consanguineous families, consistent with autosomal recessive inheritance. Mexican-Nahua sibs with facial and ophthalmologic features of FFDD type III were evaluated. Methods: Genomic DNAs were isolated for sequencing of the TWIST2 gene. The clinical features and inheritance of all previously reported FFDD patients were reviewed. Results: The affected sibs were homozygous for a novel TWIST2 frameshift mutation, c.168delC (p.S57AfsX45). Notably, both parents and two heterozygous sibs had distichiasis and partial absence of lower eyelashes. The FFDD subtypes were reclassified: the 'Brauer-Setleis' phenotype (autosomal dominant with variable expressivity) as FFDD type II; and patients with preauricular lesions as a new subtype, FFDD type IV. Conclusions: FFDD type III heterozygotes with TWIST2 mutations may have syndromic manifestations. Review of previous FFDD patients resulted in reclassification of the subtypes.